2016
DOI: 10.6018/analesps.32.3.259451
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Orientations of High-Achieving Students as Mediators of a Positive Perception of a High-Achieving Classmate: Results from a Cross-national Study

Abstract: Título: Orientaciones motivacionales de los estudiantes de alto rendimiento como mediadoras de una percepción positiva por parte de sus compañeros: resultados de un estudio transnacional. Resumen: El propósito de este estudio es explorar si las motivaciones de alto logro influencian las percepciones de los alumnos sobre un futuro compañero de clase ficticio que se caracteriza por tener un alto rendimiento; y si es así de qué modo ocurre. La muestra final consistió en 396 alumnos de alto rendimiento que fueron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Another proposal for future research is to assess the awareness of their professional skills in employees with different motivational orientations. In this regard, some recent research [33] proposes that the workmates of people with performance-avoid goal orientation have a worse perception of these people’s intellectual skills, social qualities, and popularity, which can influence the organizational climate and self-knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Another proposal for future research is to assess the awareness of their professional skills in employees with different motivational orientations. In this regard, some recent research [33] proposes that the workmates of people with performance-avoid goal orientation have a worse perception of these people’s intellectual skills, social qualities, and popularity, which can influence the organizational climate and self-knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Oh and collaborators' cross-cultural study (Oh et al, 2016), with 1794 participants from five countries, revealed that a learning-goal orientation and a performance-based approach to motivation predicted positive perceptions of a high-achieving classmates' intellectual ability in all participating countries but Peru. Though Obando's (2019) study with 268 students (age range 14-18) from the Residential Academy for the High Achievers revealed that the mastery-approach goal-a subtype of achievement goal following Elliot and Muruyama's model (Elliot & McGregor, 2001;Elliot & Muruyama, 2008)-and the incremental theory of intelligence-a subtype of Dweck and Leggett's (1988) model of implicit theories of intelligence-were predictive variables of academic resilience, with the mastery-approach goal functioning as a mediator between the incremental theory of intelligence and academic resilience.…”
Section: The Developmental Approachmentioning
confidence: 99%
“…Diverse investigations exist about the study of motivation as an essential element to understand academic performance in the university field (Gandomkar et al 2016;Oh et al 2016), and there is a consistent clear interest to know the diverse factors that can affect this process. If we start from the components that make up metacognitive learning, this indicates that the student should be able to check and mediate between their own personal intelligence and capacity.…”
Section: Introductionmentioning
confidence: 99%